Definitive Radiation Therapy for Stage I-II Endometrial Cancer: An Observational Study of Nonoperative Management. (December 2017) - Yoo, Stella; Hegarty, Sarah E.; Mishra, Mark V.; Patel, Nirav; Cantrell, Leigh A.; Showalter, Timothy N.
Abstract : Objective: There is limited evidence to inform the management of patients with endometrial cancer who are not candidates for hysterectomy, and treatment alternatives have not been compared directly in randomized trials. We analyzed the prognostic factors and outcomes for patients with stage I or II endometrial adenocarcinoma in the National Cancer Institute's Surveillance, Epidemiology, and End Results public database. Methods: We identified a cohort of patients with stage I-II endometrial adenocarcinoma who were managed without hysterectomy and who were diagnosed during 1989 to 2010. Patients with prior primary tumors were excluded. Statistical analyses were performed to test associations between patient characteristics, radiotherapy modality, and overall and endometrial cancer-specific survival. Multivariable analyses were performed to evaluate the impact of radiation therapy (RT) type on survival outcomes after adjusting for other factors. Results: Among the 997 women included in the analyses, 605 received no RT (60.7%), 207 (20.8%) received external-beam radiation therapy (EBRT) alone, and 185 (18.6%) received brachytherapy, either alone or in combination with EBRT. After adjusting for other tumor and demographic factors, RT type was not associated with overall or endometrial cancer-specific survival. Significant predictors of survival included: tumor stage and grade, age at diagnosis, and marital status. Conclusions: For patients in this population-based cohort with early-stage endometrial cancer managed without hysterectomy, the delivery of brachytherapy was not associated with improved survival, compared with EBRT alone. It seems worthwhile to pursue future clinical trials to evaluate definitive EBRT-alone strategies, omitting brachytherapy, for selected patients with medically inoperable endometrial cancer. Abstract : Supplemental Digital Content is available in the text.